2021
DOI: 10.1101/2021.05.17.443835
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

3D matrix adhesion composition facilitates nuclear force coupling to drive invasive cell migration

Abstract: Cell invasion and metastasis is a multi-step process, initialised through the acquisition of a migratory phenotype and the ability to move through differing and complex 3D extracellular environments. In this study we set out to identify the parameters required for invasive cell migration in 3D environments. Cells interact with the extracellular matrix via transmembranespanning integrin adhesion complexes, which are well characterised in cells plated on 2D surfaces, yet much less is known about them in cells em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 80 publications
(142 reference statements)
0
9
0
Order By: Relevance
“…65 In this context, Newman et al reported that MYO18Aα operates at three-dimensional level to convey integrin-associated cell-matrix interactions with nuclear movement through MYH9 across the cell. 23 Work by Yu and colleagues identified the interaction of MYO18Aɑ with the p21-activated kinase 2 (PAK2) via binding of the carboxy-terminal extension of MYO18Aɑ with the PAK-interacting exchange factor βPIX. 66 PAK2 is a regulator of actin organization and cell migration, which forms a complex with βPIX and the G-protein-coupled receptor kinase interactor 1 (GIT1), both of which localize to focal adhesions and mediate lamellipodia and membrane ruffle formation.…”
Section: Role In Cell Migration Via Interactions With Lurap1 and βPixmentioning
confidence: 99%
See 1 more Smart Citation
“…65 In this context, Newman et al reported that MYO18Aα operates at three-dimensional level to convey integrin-associated cell-matrix interactions with nuclear movement through MYH9 across the cell. 23 Work by Yu and colleagues identified the interaction of MYO18Aɑ with the p21-activated kinase 2 (PAK2) via binding of the carboxy-terminal extension of MYO18Aɑ with the PAK-interacting exchange factor βPIX. 66 PAK2 is a regulator of actin organization and cell migration, which forms a complex with βPIX and the G-protein-coupled receptor kinase interactor 1 (GIT1), both of which localize to focal adhesions and mediate lamellipodia and membrane ruffle formation.…”
Section: Role In Cell Migration Via Interactions With Lurap1 and βPixmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] MYO18Aα connects integrin-associated cell-matrix interactions with nuclear movement, a function that may take a leading role in malignant cell migration in three-dimensional matrix. 23 The role of MYO18Aα as a driver of cancer progression or suppression, however, appears to be tissue or cell typedependent that may manifest at different stages of malignancy when physiologic conditions are compromised. [24][25][26][27] MYO18A isoforms have been localized to the leading…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, the adhesion complex cannot maintain high force transmission because of an unstructured or fluidized, softened cytoskeleton [ 150 ]. Also, preliminary reports from Newman and colleagues [ 151 ] showed that IACs in protrusions enable actomyosin-mediated force transmission to the nucleus. The ECM is paramount for this mechanism because substrate rigidity directly controls when contractile forces are optimally transmitted.…”
Section: Mechanics Of Cell Migrationmentioning
confidence: 99%
“…Still, studies must be translated to 3D in vivo scenarios because of the stark differences between these two systems regarding their biochemical and biophysical properties [ 171 ]. For instance, we still do not know much about the composition, regulation, and role of IACs in 3D domains [ 122 ,, 151 ]. New protocols are required to increase our knowledge of the mechanisms of cell–matrix interactions in these more realistic environments [ 33 , 236 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation